Exploring retail orientated rotating savings and credit associations: festive season 'stokvels' in South Africa. Issue 3 (26th May 2020) - Lappeman, James; Litkie, Jemma; Bramdaw, Shriya; Quibell, Abigail
ABSTRACT: Festive season rotating savings and credit associations (ROSCAs) or 'stokvels' form a large segment of the market in the lower-income bracket and informal market sector in South Africa and have a high collective purchasing power. This study explores the multi-month, multi-phase process through which these stokvels' evaluate and purchase bulk groceries from retailers at a substantial discount during the festive season. The study followed an exploratory research design through fifteen in-depth interviews of retailers, interviews that were thematically analysed. The findings revealed four phases in festive season stokvel's buying process, namely: Need Development, Double-Evaluation Loop, List Consolidation, and Post-purchase Behavior. Each phase encapsulated a number of salient interdependent relationships and prominent time periods in which activities occurred over a year through the lens of the participating retailers. While the actual transaction happens in December, the process usually starts before April of that year. The process is modeled to show when certain phases of the process are completed as well as the actors involved (stokvel, retailer, manufacturer/supplier). To date, there has been no research that has examined the buying process of festive season stokvels through the perspective of the retailer. By creating the first map of this commercial and social process, this exploratory research paves the way for further research into the selling and buying processes in these widely used systems of group purchase.